In silico screening of identified phytochemicals from the leaf of Cipadessa baccifera (Roth.) miq. for its anti-psoriatic activity - Minautee R Patel; Amit Patel; Mukeshkumar Nariya; Rabinarayan Acharya (Wolters Kluwer Medknow Publications, 2022)
Introduction: Psoriasis (kitibha) is characterized by chronic inflammation and epidermal hyperplasia where mast cells and tryptase are activated with related form of cytokines. Cipadessa baccifera (Roth.) Miq. (Meliaceae family) is an ethnomedicinal plant reported for its anti-psoriatic tribal claim. In the present study, in silico docking study was planned for proven clinical use of C. baccifera in psoriasis with identified phytoconstituents. Methods: Eight identified well-known phytochemicals from the leaf of C. baccifera were used. The molecular docking studies were performed using iGEMDOCK2.1. Drug likeness of the compounds was predicted using Swiss ADME while in silico toxicity studies were performed using ProTox-II online tool. Results: All of retrieved eight phytoconstituents of C. baccifera possesses drug likeness properties. Phytoconstituents are nontoxic in nature and showing bioavailability, having significant inhibitory activities on validated anti-psoriatic targeted proteins, 2ZEB (Human Mast Cell Tryptase) and 2AOT (Histamine methyltransferase). Conclusion: The results of present study suggest the potential clinical role of C. baccifera in psoriatic patients and thus, proved the traditional claim through in silico docking study.